If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x+1=(x+11)/3
We move all terms to the left:
3x+1-((x+11)/3)=0
We multiply all the terms by the denominator
3x*3)-((x+11)+1*3)=0
We add all the numbers together, and all the variables
3x*3)-((x+11)=0
Wy multiply elements
9x^2=0
a = 9; b = 0; c = 0;
Δ = b2-4ac
Δ = 02-4·9·0
Δ = 0
Delta is equal to zero, so there is only one solution to the equation
Stosujemy wzór:$x=\frac{-b}{2a}=\frac{0}{18}=0$
| f−23=165 | | 40+8x=18x | | 5(k-1)+6k=83 | | 75(d+45)=315 | | 9(x-3)^2+5=905 | | -9+2x=-(=6x-4.5)+3.1 | | 4(b+4)=2(b-5) | | 5p+p+3=15 | | 3.5x+4=3x | | 9(9x+10)=414 | | 8.5=g-4.65 | | 2(75-d)=315 | | 21/56=34/d | | x+3x+100=80 | | (6x-2)+72+(11x-9)+30=180 | | -480=t+-746 | | 4+m/6=18 | | 2x5x=49 | | c+3=990 | | 2(11/31)-3y=7 | | x-13x=48 | | 3(m+4)=37 | | 4(1-7n)=-8+3(4+5n) | | 2(3x+2)+6=32 | | 12-8x=3x=12 | | 572=q-49 | | 18(2x+4)=108 | | 5x+6=566 | | 5=3(r+2) | | -(1-3a)-3a=5(3-a)-6 | | 21m=63 | | 12(x-7)=-60 |